2020
DOI: 10.3390/ijgi9050306
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Inferring Route Choice of Commuting Trip From Mobile Phone Network Data

Abstract: For billing purposes, telecom operators collect communication logs of our mobile phone usage activities. These communication logs or so called CDR has emerged as a valuable data source for human behavioral studies. This work builds on the transportation modeling literature by introducing a new approach of crowdsource-based route choice behavior data collection. We make use of CDR data to infer individual route choice for commuting trips. Based on one calendar year of CDR data collected from mobile users in Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…These losses are due to fading and multiple propagations [33]. From the studies, it has been concluded that the range of the excellent signal is between 0 and −60 dB m and for the poor signal is above −100 dB m [34], as shown in Figure 2b. The goal of the suggested research is to figure out where the best cell phone tower placement is.…”
Section: Introductionmentioning
confidence: 91%
“…These losses are due to fading and multiple propagations [33]. From the studies, it has been concluded that the range of the excellent signal is between 0 and −60 dB m and for the poor signal is above −100 dB m [34], as shown in Figure 2b. The goal of the suggested research is to figure out where the best cell phone tower placement is.…”
Section: Introductionmentioning
confidence: 91%
“…Most contributions of the work revolve around the representation of mobility and impact analysis. Experimental results show that it is possible for gathering route choice information on a large-scale road network based on route choice inference models for digital trace collection [27]. As Cats and Jenelius demonstrated, real-time information could facilitate the understanding of transport networks' vulnerability and disruptions [259].…”
Section: Impact Of Mobile Technology On Transport Systemsmentioning
confidence: 96%
“…Apart from investigating commuting behaviours and measuring the commuting distance, a commuting map also helps us to understand commuting patterns [35]. A flow map is a typical way of visualising the work-to-home journey, and it has a wide range of applications such as transportation flow and commuting flow [36][37][38][39][40][41]. Tobler [42] presented some early examples of the initial flow map to show geographical movements.…”
Section: The Origin-destination Flow Mapmentioning
confidence: 99%